Apolipoprotein B Is a Good Tool for Screening Dyslipidaemia in Apparently Healthy Population - Athiththan, L.V.; Nusha, M.F.F.; Hettiaratchi, U.P.K.; Perera, P.P.R. (Journal of Biosciences and Medicines, 2016)
Attached

Dyslipidaemia is the major risk factor for cardiovascular disease (CVD) which is the leading cause of death in the world. Even though several lipid parameters are used, currently apolipoprotein B (apoB) is considered as the best predictor of CVD. Thus this study was carried out to find out the association between conventional lipid parameters and apoB in apparently healthy subjects. A descriptive cross-sectional study was carried out in 170 apparently healthy volunteers who were not diagnosed with dyslipidaemia. After 12 hours overnight fast venous blood was obtained and Total cholesterol (TC), Triglyceride (TG), High density lipoprotein cholesterol (HDL-C) were measured by enzymatic kit method. Low density lipoprotein cholesterol (LDL-C) was calculated by Friedewald formula and apoB was analyzed by immune turbid metry using a Konelab® auto analyzer. Among the participants, majority (63.5%) were females. The mean value of apoB concentration of the population was 103 ± 42 mg/dL which was similar and not significantly different between the genders (Males, 102 ± 37 mg/dL and Females, 104 ± 45 mg/dL). All lipid parameters showed a positive correlation with apoB concentration whereas HDL-C had a negative correlation (
Keywords: Apolipoprotein B; Dyslipidaemia; High Density Lipoprotein; Low Density Lipoprotein